The effect of producer service agglomeration externalities on urban green innovation efficiency in China - Siyuan Xuan; Kaiyao Wu; Jing Deng (Heliyon, 2024)
For China's urban industrial layout and green innovation, determining which types of producer service agglomeration externalities (PSAE) are most conducive to the rise of green innovation efficiency (GIE) has theoretical and practical relevance. Based on the panel data of 274 prefecture-level cities in China from 2006 to 2019, this paper adopted the super-SBM model with unexpected output to evaluate the urban GIE. It used the Moran I index to judge the spatial auto-correlation of GIE, followed by the spatial Durbin model (SDM) to examine the spatial spillover effect of PSAE on the urban GIE. Then we used a comprehensive threshold effects model to investigate the non-linear relationship. The results demonstrate that Marshall-Arrow-Romer externality (MARE) and Jacobs externality (JACE) are curbing the urban GIE. Porter externality (PORTERE) inhibits the region and promotes the surrounding area. Furthermore, these effects also depend on the stage of economic development.